RENDIMENTO E QUALIDADE DE CANA POR MODIFICAÇÕES DE CULTIVAR E DENSIDADE DE CULTIVO - Boff, Jose T.; Kalb, Marcos A.; Quadros, Valmir J. d.; Stasiak, Mauricio; Rolim, Odair; Bernardes, Diego; Viera, Rogério; Krüger, Cleusa A. M. B.; Silva, Jose A. G. d.; Fontaniva, Cristiano (Salão do Conhecimento, 2013)
Resumo